1986
DOI: 10.1093/rheumatology/25.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis: Treatment Which Controls the C-Reactive Protein and Erythrocyte Sedimentation Rate Reduces Radiological Progression

Abstract: One hundred and fifty consecutive patients with active, rheumatoid arthritis were assessed and treated with gold, D-penicillamine, chloroquine or dapsone. Four groups were selected from these patients. Group I consisted of 60 patients who did not complete 12 months' therapy. Group II consisted of patients in whom ESR and C-reactive protein (CRP) fell to less than 30 mm/h and less than 20 mg/l, respectively, and remained at these levels between 6 and 12 months. In group IV the ESR and CRP fell but remained grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(64 citation statements)
references
References 0 publications
3
57
0
3
Order By: Relevance
“…Patients treated with MTX alone in this study also showed increasing progression of joint damage with increasing time-averaged disease activity, as reflected in the levels of acute-phase reactants and swollen joint counts. These findings are consistent with those of previous studies in which normalization of disease activity during the course of therapy was an important factor in preventing major radiographic progression (7,13,17,18). However, even in patients with persistently elevated disease activity, the use of infliximab along with optimal doses of MTX therapy significantly retarded progression of radiographic changes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients treated with MTX alone in this study also showed increasing progression of joint damage with increasing time-averaged disease activity, as reflected in the levels of acute-phase reactants and swollen joint counts. These findings are consistent with those of previous studies in which normalization of disease activity during the course of therapy was an important factor in preventing major radiographic progression (7,13,17,18). However, even in patients with persistently elevated disease activity, the use of infliximab along with optimal doses of MTX therapy significantly retarded progression of radiographic changes.…”
Section: Discussionsupporting
confidence: 91%
“…These relationships have been established from previous studies of the natural course of RA and from results of clinical trials of treatments that are no longer the standard of care (14)(15)(16). Nevertheless, it is well known that disease-modifying antirheumatic drug (DMARD) therapy can successfully interfere with disease progression and that such efficacy is particularly evident in patients with a well-controlled acute-phase response (13,17,18).…”
mentioning
confidence: 99%
“…In general, the reduction in CRP and ESR levels correlate with a decrease in clinical disease activity (32) and less joint destruction (33), although this may be due, in part, to the direct systemic effect of TNFi on hepatic synthesis of acute-phase proteins rather than a true improvement in local synovitis. In fact, CRP level is an important biomarker of radiographic progression in RA patients receiving DMARDs (methotrexate), but this predictive value disappears when RA patients are treated with TNFi (34).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that an elevated acute-phase response, especially a high CRP level, predicts subsequent radiologic damage (12). Van Leeuwen and colleagues (13) showed, in a prospective study of 149 patients with early RA, that in individual patients, time-integrated CRP values correlated closely with radiologic progression.…”
mentioning
confidence: 99%